Characterizing Unaccompanied Foreign Minors: Educational Level and Length of Stay as Individual Difference Factors That Impact Academic Self-Efficacy - Olmos-Gómez, María del Carmen; Pistón-Rodríguez, María Dolores; Chacón-Cuberos, Ramón; Romero-Díaz de la Guardia, José Javier; Cuevas-Rincón, Jesús Manuel; Olmedo-Moreno, Eva María (Frontiers in Psychology, 2022)
The aim of the present study is to analyse individual differences in academic self-efficacy within a population of Unaccompanied Foreign Minors (UFM) from the European cities of Ceuta and Melilla (Spain). Variables describing educational level and length of stay were considered in a sample of 377 individuals being cared for in different youth centres. Of these, 63.4% belonged to the group who had stayed at the Centre for less than 9 months and 36.6% reported a length of stay of more than 9 months. The age of participants ranged between 8 and 17 years old (M = 14.87 years). Once the quality parameters of the instrument (academic self-efficacy) were elaborated, reliability and validity was confirmed through Confirmatory Factor Analysis (CFA) using Structural Equation Modelling (SEM) methodology. Data collection was then initiated. The results overall indicate that 87.6% of those who completed the questionnaire reported a higher level of self-efficacy with regards to working with any classmate, whilst at the same time seeing themselves as capable of achieving good marks. ANOVA results indicated significant differences with respect to educational level and length of stay. In this regard, students who had received professional training and had been at the Centre for more than 9 months, were the ones who developed greater academic self-efficacy for spending more time working when tasks were judged to be difficult. The results obtained demonstrate that any intervention will be positive as long as it promotes different institutions to develop strategies that cater to a length of stay of more than 9 months and target education, academic self-efficacy, socialisation and strengthening the future workforce. Such interventions can be directed through new European, Spanish or local level policies. It is clear that institutions still have a lot of work left to do.